Learner- or Teacher-centered Instruction: Student Teachers' Preference and the Role of Their English Proficiency - ., Kusumarasdyati (KnE Social Sciences, 2023)
Abstract. EFL student teachers should support learner-centered approach to learning because it developed autonomy and benefited them in life-long pursuit of knowledge. However, anecdotal evidence showed that some student teachers still preferred teacher-centered approach. This mixed-method study was conducted to find out: (1) whether there was a significant relationship between the preference of learner- or teacher-centered instructions and the student teachers’ English proficiency; and (2) why student teachers support teacher-centered instruction. Numeric data were collected from 51 participants by means of a structured questionnaire and test of English proficiency (TEP), whereas the qualitative data were obtained from an unstructured questionnaire and semi-structured interviews. The results showed that the preference of learner- or teacher-centered instructions were not significantly associated with their English proficiency. In addition, the student teachers preferred teacher-centered instruction for three reasons, fixed mindset, difficulties in understanding materials, and comprehensible explanations given by the teacher educators. Based on these findings, further research about this issue was recommended. Keywords: learner-centered instruction, teacher-centered instruction, English proficiency, student teachers